The Effect of Financial Performance on Stock Prices: Empirical Evidence from Building Construction Sub-Sector Companies: Article - Christina Heti Tri Rahmawati; Sri Hartuti; Maria Theresia Ernawati (Eastasouth Institute, 2022)
The company's financial performance is an assessment of the financial condition of investors when they invest their capital. The purpose of this study is to measure the effect of financial performance using liquidity, profitability and solvency ratios on stock prices of building construction sub-sector companies listed on the Indonesia Stock Exchange for the period 2014-2020 either simultaneously or partially. This study has a population of 18 companies listed in the building construction sub-sector on the IDX. This study uses a sampling technique, namely purposive sampling, where the sampling criteria are in the form of an annual report and have data on stock market prices continuously during the study period. study uses data analysis techniques in the form of multiple linear regression analysis with SPSS Version 25 applicationThe implication of the results of this study for investors should look at the company's solvency ratio before making a stock purchase, so that the greater the solvency ratio can increase the company's stock price.